Age-related decline in Olympic triathlon performance: Effect of locomotion mode - Bernard, T.; Sultana, F.; Lepers, R.; Hausswirth, C.; Brisswalter, J. (Experimental Aging Research, 2009)
This study describes the decline in performance with age during Olympic triathlon Age Groups World Championships among the different locomotion modes. Mean performance of top 10 performers were analyzed for each group of age using the exponential model proposed by Baker, Tang, and Turner (2003, Experimental Aging Research, 29, 47-65). Comparison in performance decline was done between locomotion modes. Decline in performance in triathlon as a function of age follows an exponential model. A significant interaction effect between age and locomotion mode was observed on performance values. In swimming, a significant decrease was observed close to 5% per year after 45 years. Decline in performance was less pronounced in cycling until 60 years. Analysis of the effect of age in the different locomotion modes of a triathlon could provide information for maintaining quality of life with aging.